36 Million language pairs - Petzold Thomas (Cultural Science)
This article provides an overview on some of the key aspects that relate to the co-evolution of languages and its associated content in the Internet environment. A focus on such a co-evolution is pertinent as the evolution of languages in the Internet environment can be better understood if the development of its existing and emerging content, that is, the content in the respective language, is taken into consideration. By doing so, this article examines two related aspects: the governance of languages at critical sites of the Internet environment, including ICANN, Wikipedia and Google Translate. Following on from this examination, the second part outlines how the co-evolution of languages and associated content in the Internet environment extends policy-making related to linguistic pluralism. It is argued that policies which centre on language availability in the Internet environment must shift their focus to the dynamics of available content instead. The notion of language pairs as a new regime of intersection for both languages and content is discussed to introduce an extended understanding of the uses of linguistic pluralism in the Internet environment. The ultimate extrapolation of such an enhanced approach, it is argued, centres less on 6,000 languages but, instead, on 36 million language pairs. This article describes how such a powerful resource evolves in the Internet environment.